BENEFICIAL EFFECTS OF SILICON FERTILIZERS ON INDICATORS OF SEED GERMINATION, BIOMASS AND GRAIN YIELD OF BARLEY, SOYBEAN AND CORN - Revtie-Uvarova, Alina; Miroshnychenko , Mykola; Hladkikh , Yevheniia; Siabryk , Olesia; Voitovych , Olena (Journal of Agricultural Sciences (Belgrade), 2023)
The main purpose of the study was to determine the optimal doses and methods of applying silicon fertilizers under barley, corn and soybeans in the soil and climatic conditions of Ukraine. A series of laboratory experiments, field experiment and statistical-analytical data processing were carried out. The small-plot field experiment was conducted on the condition of a long-term research field trial on chernozem podzolic of the NSC "Institute for Soil Science and Agrochemistry Research named after O.N. Sokolovsky" (Kharkiv region, Forest-Steppe of Ukraine). The laboratory experiments was set up in Petri dishes with using preparative form of different concentration (0.5%, 0.75% and 1.0%) of potassium silicate for their assess on germination indicators of seeds of barley and corn. The significant stimulating effect of potassium silicate on the germination rates of barley and corn seeds was proved; the optimal concentration of the solution for pre-sowing seed treatment was established. A close positive correlation was determined between the amount of SiO2 application and the yield of the studied crops (P
Keywords: silicon; plant nutrition; crop productivity; mineral fertilizer